High level Antarctic EIA under the Madrid Protocol: state practice and the effectiveness of the Comprehensive Environmental Evaluation process - Alan Hemmings; Lorne Kriwoken
Antarctica, Antarctic Treaty system, International environmental management, Environmental impact assessment, Effectiveness of multilateral environmental agreements